Edukasi Pencegahan Pernikahan Dini Sebagai Upaya Pencegahan Stunting Melalui Bimbingan Konseling Klasikal Pada Remaja - Zuhdi Zainul Majdi, M. (Institut Agama Islam Hamzanwadi NW Pancor, 2024)
Stunting is a condition in which a person's height is less than normal according to gender and age. The influence of stunting affects the next generation and the inhibited development of the verbal and cognitive motor side. To prevent the occurrence of stunting can be done with the implementation of classical format counselling services for prevention of early marriage as a stunting prevention effort. The target of this activity is the people of the village of Sembalun Sajang. The aim of the event is to raise public awareness of early marriage prevention as a stunting prevention effort. The method used in the activity is socialization with data collection techniques such as observations and interviews. Data analysis was carried out on pre-test and post-test results to see if there were any changes in the understanding of early marriage prevention as a stunting prevention effort. The results of this activity show that the implementation of classical format counselling services has influenced on improved understanding related to early marriage prevention as a stunting prevention effort